Can Slow Breathing Exercise Reduce Blood Pressure In Elderly People With Hypertension in UPT PSTW Banyuwangi? - Izza, Inayah Ageng; Fahruddin, Sri Gunda Fahriana; Dewi, Ketut Laksmi Puspa (Open Access Health Scientific Journal, 2025)
Background: Hypertension is one of the leading causes of morbidity and mortality worldwide. High blood pressure (BP) is a non-communicable disease that is a risk factor for cardiovascular disease. Non-pharmacological treatments, such as slow breathing exercise (SBT), have been shown to lower blood pressure. the purpose of this study was to analyze the effect of slow breathing exercise on lowering blood pressure in elderly hypertension.Method: This research is an experimental study with the research design used is one group pre-test and post-test with control group. The population in this study were all elderly people who lived in UPT PSTW Banyuwangi with a research sample of elderly people suffering from hypertension. Sampling using purposive sampling method and obtained 36 respondents. Respondents were divided into 2 groups, which were the treatment group with slow breathing exercise intervention and the control group without any intervention. blood pressure was measured before and after treatment using an aneroid tensimeter. the data was collected then processed and analyzed using SPSS with the test used, namely the Wilcoxon test.Results: Based on the results of statistical tests using the Wilcoxon test, a significance value of p <0.05 was obtained, which means that slow breathing exercise has an effect on lowering blood pressure in hypertensive elderly people. the application of slow breathing exercise is also more effective than in the control group, characterized by a difference in the mean pre-test and post-test values of 8.88 mmHg.Conclusion: slow breathing exercise has an effect on lowering blood pressure in hypertensive elderly people so that this can be used as a non-pharmacological therapy as an effort to control or lower blood pressure in hypertensive elderly people and its application is very easy to do.